Evaluation of Safety and Pharmacokinetic Behavior of Unipeg® in Healthy Human Volunteers - T. Ahmad; R. Ahsan; M.R. Raza; G. Saba (Journal of Pharmacy and Nutrition Sciences, 2014)
Peginterferon α-2a (20 kDa) derived from Hansenula Polymorpha is a distinct variety of peginterferons (PEG-IFN). A pilot study of this drug was conducted on healthy human subjects to evaluate its safety and pharmacokinetic behavior in local population. With due approval of the IEC operating under ICH-GCP guidelines; ten healthy male subjects were selected randomly from the Pakistani population after thorough screening and signing of the Informed consent for an open label, single dose study. Each subject received a subcutaneous injection of the drug (180 µg) in abdominal skin and blood samples were collected at 0 and 1, 2, 3, 6, 12, 24, 36, 60, 84, 108, 132 and 156 hours, and analyzed by a validated ELISA method for peginterferon α-2a (20kDa), Unipeg®. The Mean ± SEM (standard error of mean) PK parameters were found to be: Cmax: 18.67±2.92 ng/ml (7.05-34.51); AUC0-∞: 1440±113 h.µg/l] (969-2101); Absorption Half-Life: 17.02±2.06 h (10.37-29.26), elimination half life: 41.437±6.21 h (18.51-78.97 h); volume of distribution 8.933±1.72 L (4.81-18.34), clearance: 112.6±8.21 ml/h (71.96–155.96). The safety of the drug was evaluated by observation of adverse effects and evaluating the change in general health parameters, hematological and biochemical test results during and after the study. No Sever Adverse Effect was observed however the most common adverse event (AE) was the fever; observed in all volunteers (n=10), headache (6), Fatigue (5), Vomiting (4) and diarrhea, loss of appetite, body ache was observed in 3 volunteers. Three out of ten volunteers demonstrated decrease in WBC and platelets count. Changes observed in hematology returned to normal values within 16 days. The safety profile of UNIPEG® was found to be very similar to those of reported in literature for unmodified IFNs and other pegylated interferons generally used in therapy. Future clinical trials are recommended to further establish the safety profile and pharmacokinetics.